2021
DOI: 10.1016/j.asmr.2021.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Biomechanics, and Pathologies of the Meniscofemoral Ligaments: A Systematic Review

Abstract: Purpose: To systematically review the literature to examine current understanding of the meniscofemoral ligaments (MFLs), their function, their importance in clinical management, and known anatomical variants. Methods: A systematic review was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines using PubMed, EMBASE, and Cochrane databases. Studies were included if they reported on the biomechanical, radiographic, or arthroscopic evaluation of human MFLs, or if they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…The reported prevalence of an MFL is inconsistent. In their systematic review, Deckey et al reported that a posterior MFL was present in 24-86% of patients conirmed by the cadaveric study and in 11.9-78.3% in the MRI study [6]. In the present study, 22.2% of patients with symptomatic DLM did not have an MFL, but the efect on extrusion was small.…”
Section: Discussionsupporting
confidence: 51%
“…The reported prevalence of an MFL is inconsistent. In their systematic review, Deckey et al reported that a posterior MFL was present in 24-86% of patients conirmed by the cadaveric study and in 11.9-78.3% in the MRI study [6]. In the present study, 22.2% of patients with symptomatic DLM did not have an MFL, but the efect on extrusion was small.…”
Section: Discussionsupporting
confidence: 51%
“…However, the stability of the LM is crucial for maintaining its biomechanical function. This is attained through bony support by the lateral tibial plateau, integrity of the meniscofemoral ligaments (MFL) and anchoring of its roots [10, 14, 18, 24]. In terms of the correlation between injuries of the LM and PLTP impression fractures, Bernholt et al [4] found an increased incidence of LM tears in patients with depressed fragment fractures (IIIB), as well as an increased incidence of lateral meniscus posterior horn and root lesions in patients with shear fragment fractures (IIIA).…”
Section: Discussionmentioning
confidence: 99%
“…Commonly in different sports players, overuse injuries of the medial collateral ligament can ensue and cause joint instability. 19 Involvement of the meniscofemoral ligament is more frequent and dynamic examination under valgus stress would be noteworthy, especially for partial-thickness tears. Further detailed examination of this area can be done as described previously, also/especially the histological junction between the medial meniscus and the meniscofemoral or meniscotibial ligament after trauma.…”
Section: Clinical Indications Medial Collateral Ligament Injurymentioning
confidence: 99%
“…Commonly in different sports players, overuse injuries of the medial collateral ligament can ensue and cause joint instability 19 . Involvement of the meniscofemoral ligament is more frequent and dynamic examination under valgus stress would be noteworthy, especially for partial-thickness tears.…”
Section: Medial Viewmentioning
confidence: 99%
See 1 more Smart Citation